TOOLS VALUE ANALYSIS IN COMMERCIAL BANKS - Tatyana Zakharova (Вестник Северо-Кавказского федерального университета)
Indicator of the effectiveness of the Bank, its competitiveness is cost, in connection with which the Bank must determine the hidden reserves, to choose options of mitigation, change the ratio between useful and excessive costs total labour, i.e. the Bank needs to assess the real cost of banking services without regard to the organizational structure. In this context, value analysis of the cost of banking services is an important activity.